Analisis Kinerja Pelayanan Ibadah Haji Dan Umrah Dalam Membangun Citra Positif - Muchlis Essa (Multazam : Jurnal Manajemen Haji dan Umrah, 2022)
The purpose of this research is to find out how well Daqu Travel is in building a positive image of the company through the provision of Hajj and Umrah services. A descriptive qualitative research method was used for this research. According to research findings, the Daqu Travel company implements a service performance method to produce high-quality services by offering the greatest possible level of service to pilgrims. Services that will enhance the reputation of the company's products, as well as services that will build emotional relationships between the company and its employees and staff, as well as alumni and prospective pilgrims. In addition to that, Daqu Travel's service performance is a positive image of the company that looks good with testimonials from pilgrims or alumni of the congregation, and the response or stimulus given is positive. The satisfaction communicated by these testimonies has contributed to the continued increase in the number of pilgrims attending this event year after year.